The Remitting Patterns of African Migrants in the OECD - Bollard, Albert (2012)
Recorded remittances to Africa have grown dramatically over the past decade. Yet data limitations still mean relatively little is known about which migrants remit, how much they remit, and how their remitting behavior varies with gender, education, income levels, and duration abroad. This paper constructs the most comprehensive remittance database on immigrants in the OECD currently available, containing microdata on more than 12,000 African immigrants. Using this microdata the authors establish several basic facts about the remitting patterns of Africans, and then explore how key characteristics of policy interest relate to remittance behavior. Africans are found to remit twice as much on average as migrants from other developing countries, and those from poorer African countries are more likely to remit than those from richer African countries. Male migrants remit more than female migrants, particularly among those with a spouse remaining in the home country; more-educated migrants remit more than less educated migrants; and although the amount remitted increases with income earned, the gradient is quite flat over a large range of income. Finally, there is little evidence that the amount remitted decays with time spent abroad, with reductions in the likelihood of remitting offset by increases in the amount remitted conditional on remitting.